2011
DOI: 10.1038/oby.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Maternal Depression and Family Structure on Child BMI: Parenting Quality and Risk Factors for Child Overweight

Abstract: Risk factors for child obesity may be influenced by family environment, including maternal depression, family structure, and parenting quality. We tested a path model in which maternal depression and single parent status are associated with parenting quality, which relates to three risk factors for child obesity: diet, leisure, and sedentary behavior. Participants included 4,601 5th-grade children and their primary caregivers who participated in the Healthy Passages study. Results showed that associations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 57 publications
1
73
2
5
Order By: Relevance
“…Prenatal exposure to maternal stress and distress has been shown to be associated with both children's obesity and rapid postnatal growth (108,109). Proposed mechanisms for the association include infant feeding practices (110), mother-infant interaction (111), mother-infant feeding interactions (112), parenting style (113), and a direct effect of stressors leading to central adiposity via arousal of the child's hypothalamic-pituitary-adrenal axis (86). It has also been suggested that, due to the comorbidity between maternal overweight and emotion regulation, these pathways may also play into the intergenerational transfer of overweight and obesity (112), as well as the roles of shared genes and environment (86).…”
Section: Psychosocial Vulnerabilitiesmentioning
confidence: 99%
“…Prenatal exposure to maternal stress and distress has been shown to be associated with both children's obesity and rapid postnatal growth (108,109). Proposed mechanisms for the association include infant feeding practices (110), mother-infant interaction (111), mother-infant feeding interactions (112), parenting style (113), and a direct effect of stressors leading to central adiposity via arousal of the child's hypothalamic-pituitary-adrenal axis (86). It has also been suggested that, due to the comorbidity between maternal overweight and emotion regulation, these pathways may also play into the intergenerational transfer of overweight and obesity (112), as well as the roles of shared genes and environment (86).…”
Section: Psychosocial Vulnerabilitiesmentioning
confidence: 99%
“…Maternal depression, which is estimated to afflict 14 % of women of reproductive age [12], has been implicated as a potential risk factor for childhood overweight and obesity [22]. The relationship of maternal depression and childhood overweight/obesity has been hypothesized to be associated with parenting practices [16], as depressed mothers may have difficulty sustaining exclusive breastfeeding [1], recognizing child satiety cues [18,19], providing healthful food choices [18,24], and modeling physical activity behaviors relative to non-depressed mothers [23]. Maternal depression also increases risk for depression in children [5,14,15], which may in turn influence children's weight [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some research suggests that parenting quality may partially mediate associations between maternal depression and elementary-school children's BMI (14) . One study of elementary-school children found links between maternal depressive symptoms and children's BMI, with some evidence that unhealthy eating habits partially mediated this association among boys (32) , but research on the dietary mechanisms during the developmentally important early childhood period remain unexplored.…”
mentioning
confidence: 99%
“…Mothers' depressive symptoms may affect parenting behaviours related to children's eating habits or physical activity in ways that may contribute to obesity among their children (14) . For example, some studies show that mothers exhibiting depressive symptoms have a lower likelihood of breast-feeding (15) .…”
mentioning
confidence: 99%